Questioning performance measurement metrics, organizations and power - Redden, Guy (Los Angeles SAGE, 2019)
Questioning Performance Measurement: Metrics, Organizations and Power is the first book to interrogate the organizational turn towards performance metrics critically. Performance measurement is used to evaluate a diverse range of activities throughout the private, public and non-governmental sectors. But in an increasingly data driven world, what does it really mean to measure 'performance'? Taking a sociology of quantification perspective, this book traces the rise of performance measurement, questions its methods and objectivity, and examines the social significance of the flood of numbers through which value is represented and actors are held accountable. An illuminating read for students, scholars and practitioners across Organization Studies, Sociology, Business and Management, Public Policy and Administration. --Provided by publisher.
The performance revolution -- What is performance measurement? Nuts, bolts and critical issues -- Perspectives on performance measurement -- Making the numbers : performance measurement in business -- Magical numbers : performance measurement and public goods -- Rethinking performance culture.
Includes bibliographical references (pages [117]-136) and index.
Keywords: Performance -- Measurement; Performance -- Management